Detection of tuberculosis and other infections during the COVID-19 pandemic - S. V. Kandrychyn (Туберкулез и болезни лёгких)
Based on 12 publications, official data on the detection of cases of tuberculosis and other infectious diseases in England and Wales, Germany and South Korea in 2020 and 2019 were compared. The results indicate that during the COVID-19 pandemic, there is a decrease in the number of detected cases of all major infectious diseases, and the percentage of reduction in tuberculosis detection is lower versus other infections.